Linking transdisciplinary research projects with science and practice at large: Introducing insights from knowledge utilization. Issue 102 (December 2019) - Hoffmann, Sabine; Thompson Klein, Julie; Pohl, Christian
Highlights: Empirical studies show a persistent 'project-to-science-and-practice-at-large-gap'. The field of knowledge utilization offers promising insights to address this gap. Jahn's model of transdisciplinary research prompts our revised conceptual model. Our model broadens the interactive and iterative nature of transdisciplinary research. Abstract: Recent empirical studies show a persistent gap between 'socially robust' knowledge produced by transdisciplinary research projects and its ability to promote change on a large scale. Current discourses about the 'project-to-science-and-practice-at-large gap' have focused mainly on exploring various conditions that need to be fulfilled to produce 'socially robust' knowledge. Yet, those discourses have rarely built on the broader literature of knowledge utilization, whichGreenhalgh and Wieringa (2011) emphasize acknowledges 'the fundamentally social ways in which knowledge emerges, circulates, and gets applied in practice.' Their insights are helpful in advancing our understanding of why transdisciplinary research projects do or do not contribute to sustainability on a large scale. ExpandingJahn et al. (2012)'s model of transdisciplinary research, we present a revised conceptual model of an ideal-typical, interactive and iterative transdisciplinary research process that adds two new phases from the field of knowledge utilization to their original three-phase model and accounts for the social and relational nature of knowledge utilization. The revised model includes five phases through which transdisciplinary projects operate in different order: (i) defining sustainability problems, (ii) producing new knowledge, (iii) assessing new knowledge, (iv) disseminating new knowledge in realms of both science and practice and (v) using new knowledge in both realms.